A compilation of COVID-19 psychorducation cartoon (Kuliyyah of Islamic Revealed Knowledge and Human Sciences, 2021)
The cartoons are drawn not to be guidelines. This cartoon is also not meant to cause panicking situations. The aim of the author is more on describing the actual reality in some specific contexts, especially in education and family settings, which is closer to the author himself